Molecular dynamics modeling and simulations of carbon nanotube-based gears - Yeak Su Hoe,; Che Lokman Jaafar,; Ng, Teng Yong (Universiti Kebangsaan Malaysia, 2012)
A molecular dynamics (MD) modeling method was applied to investigate the properties of carbon nanotube-based gears (CNT gears). The Brenner’s reactive hydrocarbon potential was used in order to calculate the short range interatomic forces. The Lennard-Jones 6-12 (LJ) was used to calculate the long range van der Waals potential for intermolecular interactions between gears. One gear was powered by forcing the atoms near the end of the first CNT to rotate, and a second gear was allowed to rotate by keeping the atoms near the end of second CNT constrained to a cylinder. We used the hybrid minimization to simulate the CNT-gears by coupling the unconstraint conjugate gradient minimization with the one-dimensional minimization, Brent’s method. The hybrid minimization was successfully implemented by introducing two regions in CNT gear. The switch function will affect the smoothness of the gear rotation. The switch function also affects the minimization process where simulation time will be reduced.